CO2 capture and sequestration in porous media with SiO2 aerogel nanoparticle-stabilized foams. (15th September 2022) - Du, Liping; Lu, Teng; Li, Binfei
Highlights: The fluid configured with SiO2 aerogel nanoparticles show excellent ability to capture CO2 . SiO2 aerogel nanoparticles enhanced the stability of foam. Aerogel nanofluids increase the CO2 sequestration rate in the formation. Abstract: Enhanced oil recovery (EOR) via carbon dioxide (CO2 ) flooding has been considered an economically feasible method for carbon sequestration. However, due to premature gas channeling that results in escape of a great deal of CO2, the degree of crude oil recovery is low, and the carbon sequestration effect is poor. In this paper, the process of CO2 sequestration was studied from a novel perspective by combining a SiO2 aerogel and a foam for oil displacement to reduce carbon emissions. The CO2 absorption capacities of aerogel nanofluids were tested with different concentrations (0.5–1.0 wt%) and rotational speeds (140–525 r/min). The effects of hindering gas channeling and carbon sequestration in three different flooding modes were evaluated via one-dimensional sandpack flooding experiments. The mechanism for CO2 capture by aerogels in porous media was explored through microscopic visualizations of displacement experiments. The results showed that the CO2 absorption capacity of aerogel nanofluids far exceeded those of water and conventional nanofluids. The CO2  + nanofluid displacement evidently controlled gas channeling and improved CO2 sequestration by forming stable foams, and the final sequestration rate was 60.8%. Moreover, compared with conventional foams, a model was proposed to describe different states of CO2 (dissolved, adsorbed, and free) in aerogel nanoparticle-stabilized foam displacement.